Municipal solid waste (MSW) incineration fly ash as an important source of heavy metal pollution in China - Wang, Ping; Hu, Yuanan; Cheng, Hefa (Environmental pollution (1987), 2019)
Incineration has overtaken landfilling as the most important option for disposal of the increasing volumes of municipal solid waste (MSW) generated in China. Accordingly, disposal of the incineration fly ash, which is enriched with a range of heavy metals, has become a key challenge for the industry. This review analyzes the temporal and spatial trends in the distributions of As, Cd, Cr, Cu, Ni, Pb, Zn, and Hg in MSW incineration fly ash between 2003 and 2017, and estimates the inventories of heavy metals associated with the fly ash and the average levels of heavy metals in Chinese MSW based on their mass flow during MSW incineration. It was estimated that MSW incinerators in China released approximately 1.12 × 102, 2.96 × 103, 1.82 × 102, 3.64 × 104, 1.00 × 102, 7.32 × 103, 2.42 × 102, and 1.47 × 101 tonnes of Cd, Pb, Cr, Zn, Ni, Cu, As, and Hg, respectively, with the fly ash in 2016. Due to the much greater fly ash generation rate, the incinerators based on circulating fluidized bed combustor (CFBC) technology released more heavy metals during incineration of MSW compared to those based on grate furnace combustor (GFC) technology. Results of mass-flow modeling indicate that the geometric mean contents of Cd, Pb, Cr, Zn, Ni, Cu, As, and Hg in Chinese MSW were 3.0, 109, 101, 877, 34, 241, 21, and 1.7 mg/kg, respectively, which are comparable to those in the MSW from other countries. To protect the environment from the significant potential ecological risk posed by heavy metals in the mismanaged fly ash, strict regulation enforcement and compliance monitoring are necessary to reduce the heavy metal pollution brought by improper disposal of MSW incineration fly ash, and more research and development efforts on advanced technologies for stabilization of heavy metals in fly ash and its environmentally sound reuse can help mitigate its environmental risk. [Display omitted] •Incineration is taking greater importance in municipal solid waste disposal in China.•Incineration fly ash is an important source of heavy metal pollution in the country.•Incineration fly ash is largely mismanaged, posing significant environmental risk.•CFBC incinerators release more heavy metals during incineration than GFC incinerators.•Development of proper stabilization and reuse technologies for fly ash is needed. MSW incineration fly ash, which is largely mismanaged in China, is a significant source of heavy metals, and its proper stabilization and reuse is necessary to protect the environment.